Republic of Congo : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper on the Republic of Congo analyzes the challenges of sustainable growth in the Republic of Congo. The paper highlights that it is paramount for the authorities to avoid repeating the experience of the 1980s, particularly in light of the projected decline in oil production over the next decade. It proposes a macroeconomic policy strategy that takes advantage of this unique opportunity to foster higher sustainable growth. The paper also provides a summary of various recent assessments of the quality of the Congo's public financial management system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet